1994
DOI: 10.1136/bmj.308.6930.692
|View full text |Cite
|
Sign up to set email alerts
|

Skin test reactivity and number of siblings

Abstract: * Detecting urinary tract infection in early childhood is important for preventing renal damage * Suprapubic aspiration of urine is considered in Britain to be a difficult technique * This study showed that use of ultrasound guidance makes suprapubic aspiration in children and babies easy and safe * Low bacterial counts were present in the urine of two fifths of the children with abnormalities ofthe urinary tract * Clinicians should regard low bacterial counts as important had vesicoureteric reflux. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
222
6
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(265 citation statements)
references
References 13 publications
27
222
6
8
Order By: Relevance
“…This was first postulated by Strachan (2), who found the prevalence of hay fever and atopic dermatitis (AD) to be inversely related to the number of older siblings. Similar associations have been reported since (1,3,4). This effect has been tentatively explained by the greater chances of cross-infection from older siblings in large families, which may have an important protective role in the expression of atopy: the so-called sibling effect.…”
supporting
confidence: 62%
“…This was first postulated by Strachan (2), who found the prevalence of hay fever and atopic dermatitis (AD) to be inversely related to the number of older siblings. Similar associations have been reported since (1,3,4). This effect has been tentatively explained by the greater chances of cross-infection from older siblings in large families, which may have an important protective role in the expression of atopy: the so-called sibling effect.…”
supporting
confidence: 62%
“…[1][2][3][4][5][6] Some studies have also shown that these disorders are inversely associated with child care attendance outside the home, [6][7][8][9][10] whereas other studies have not been able to confirm these findings. [11][12][13] A common interpretation of these results has been that older siblings and child care attendance are indirect measures of earlylife infections and that early-life infections have a preventive effect on the development of atopic disorders.…”
mentioning
confidence: 53%
“…The indexes to evaluate the sanitation in infancy include residence, farm living history, number of siblings, birth order, exposure to animals, parasite infestation, and so on. Studies demonstrated that farm living (von Mutius and Vercelli, 2010), more siblings (von Mutius et al, 1994), later birth order (Matricardi et al, 1998), more exposure to pets (Apter, 2003), exhibited lower prevalence of allergy and autoimmune diseases. In developing countries and rural environment, the microbial diversity is higher and the opportunity to exposure to microorganisms is more adequate.…”
Section: Hygiene Hypothesis For Admentioning
confidence: 99%